Ethnobotanical Study of Herbal Plants â€œJamuâ€ for Postpartum Mothers in Payudan Dundang Sumenep Regency - Adji, Findo Bayu; Chamisijatin, Lise; Husamah, H.; Purwanti, Elly; Nuryady, Moh. Mirza (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2024)
The society in the village of Payudan Dundang, Guluk-guluk sub-district, Sumenep still relied on plants as medicine to treat various types of diseases, particularly as herbal ingredients for postpartum mothers in order to expedite the healing process. This study aimed to identify the species of plants used for this purpose, determine the specific parts utilized, as well as explore the management and utilization of these traditional medicinal plants for postpartum mothers. This study employed a qualitative research design, utilizing interviews as the primary method of data collection. The collected data was then analyzed descriptively and grouped in tabular form. The findings of the study revealed a total of 13 plant species that were used and utilized as herbal remedies for postpartum mothers. These plants included Temulawak, Belungas, Mengkudu, Legundi, Senggugu, Kesembuen, Kunyit, Kencur, Jahe, Meniran, Mimba, Kumis Kucing, and Ceppeuh. The plant parts that were commonly used included leaves, rhizomes, and fruit. In the village of Payudan Dundang, it was reported that individuals consumed these herbal concoctions three times a day, typically in the form of tea. The benefits of these herbal remedies included restoring energy levels after childbirth, facilitating postpartum blood flow, alleviating post-delivery pain, enhancing breast milk production, and increasing the mother’s appetite.